A Suspected Complication of Radial Access Gone Good - Krzywicki P; Wąsek W; Horszczaruk G (Annals of Circulation - Peertechz Publications, 2017)
A female patient, 43 years of age, was scheduled for coronary angiography due to suspicion of coronary heart disease on the basis of cardiovascular risk factors: obesity, arterial hypertension,  hypercholesterolemia, CCS II angina and positive ECG exercise test. Due to standard protocol, a radial 6F sheath (Balton, Warsaw, Poland) was introduced into right radial artery (RA), then 5000 U of unfractionated heparin and 200μg of gliceryl trinitrate were administered intraarterially. Angiography of the right coronary artery was performed employing Judkins 4, 5F diagnostic catheter (Cordis, Miami, Fl). Because of marked arterial spasm the catheter was slowly withdrawn with inadvertent removal of the guidewire from the RA.